OPTIMALISASI PEMANFAATAN ASET TANAH PEMERINTAH KoTA MALANG MELALUI PENGGUNAAN DANA CORPORATE SOCIAL RESPONSIBILTY (cSR) - Rendra Kurnia Wardana (ipdn, 2018)
This research aims to know the optimization of land asset utilization through Corporate Social Responsibility (CSR). Land assets prioritized is an asset in the form of city parks that still not yet utilized well which become opportunities for companies to offer the CSR programs as a form of social responsibility to the environment, in addition to as active participation from the corporate world together with local governments to realize the synergy of sustainable regional development. Research methods use descriptive qualitative. The results showed that CSR is becoming an alternative financing in regional development in addition to APBD (Revenue Budget Shopping Area). Limitation of the budget the Government makes local governments innovating to find sources of financing a legitimate alternative in regional development acceleration. Keywords: asset management, corporate social responsibility, regional development innovation